(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The Internet of Things (IoT) networks, including their design, applications, future directions, difficulties, and constraints, are thoroughly discussed in this research study. The explanation of IoT networks’ design, covering definitions and components, as well as centralized and decentralized networks, follows an overview of IoT networks’ significance. The applications of IoT networks are examined in the next part, along with specific use examples from the fields of healthcare, manufacturing, transportation, and smart cities. The following section of the article examines new developments in IoT networks, including edge computing, 5G networks, AI, and blockchain technology. The difficulties and constraints of IoT networks, such as security and privacy issues, interoperability and compatibility problems, scalability, and network congestion, are also examined. The final section of the study summarizes the main ideas and research conclusions, highlighting the significance of IoT networks in our increasingly linked society.